Penyuluhan Edukasi Penggunaan Earphone Pasien Poli THT-KL RSUD dr H. Abdul Moeloek Provinsi Lampung Tahun 2024 - Akbar, Tasya; Imanto, Mukhlis (CV. Jasa Sukses Abadi, 2024)
One of the five main senses in humans is the ear which is very necessary to capture the communication delivered. The human ear can only receive sound frequency intensity with a range of about 20 Hz to 20kHz. If the ear is exposed to quite loud noise and for a long period of time, it will cause noise-induced hearing loss. Earphone users who use the device more than 8 hours / week compared to earphone users with a time limit of only a few hours, the results of hearing levels are worse. This activity aims to provide knowledge about education in the use of earphones which is carried out by the ENT-HN Polyclinic of Dr. H. Abdul Moeloek Hospital, Lampung Province. The activity began with providing counseling and continued with a discussion session. Before and after the counseling, a pre- and post-test was given with an average result of 50 and 82.5, there was a significant increase in knowledge in patients about ear health. Through this activity, it is known that there is an increase in knowledge from patients at the ENT-HN Polyclinic of Dr. H. Abdul Moeloek Hospital, Lampung Province regarding education in the proper use of earphones in everyday life.